2019
DOI: 10.3892/etm.2019.7718
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of miR‑3934‑5p enhances A549 cell sensitivity to cisplatin by targeting TP53INP1

Abstract: Tumor protein p53-inducible nuclear protein 1 (TP53INP1) is a tumor suppressor associated with malignant tumor metastasis. In addition, it has been reported that hsa-microRNA (miR)-3934 serves key roles in various types of lung cancer, including small-cell lung carcinomas (SCLC) and non-SCLC (NSCLC). Therefore, the present study aimed to determine the effects of miR-3934-5p on cell proliferation and apoptosis, and on sensitivity to cisplatin (DDP). Reverse transcription-quantitative polymerase chain reaction a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…In addition, it was shown that miR-3934-3p downregulated TGFBR1 and SMAD3. In a similar vein, HSV-1 viral infection led to a significant down-regulation of these targets [74]. Moreover, the activation of the TGF-β/Smad pathway is critical for lung fibrosis, which was previously shown in SARS-CoV-related cases.…”
Section: Mir-3934-3psupporting
confidence: 61%
See 1 more Smart Citation
“…In addition, it was shown that miR-3934-3p downregulated TGFBR1 and SMAD3. In a similar vein, HSV-1 viral infection led to a significant down-regulation of these targets [74]. Moreover, the activation of the TGF-β/Smad pathway is critical for lung fibrosis, which was previously shown in SARS-CoV-related cases.…”
Section: Mir-3934-3psupporting
confidence: 61%
“…Moreover, it has been reported that miR-3934-5p expression significantly increases in NSCLC cell line A549 [73]. It is also a SNP linked to TGF-β signalling and has been identified as downregulated in rectal carcinoma mucosa, compared with normal mucosa [74].…”
Section: Mir-3934-3pmentioning
confidence: 99%
“…Most earlier studies of miR-3934 investigated its role in cancer. For example, it was reported that miR-3934 is up-regulated in colorectal cancer cells [29] and that down-regulation of miR-3934-5p may enhance the sensitivity of A549 non-small cell lung cancer cells to cisplatin by targeting TP53INP1 [30]. Here, we observed that miR-3934 is significantly down-regulated in PBMCs from asthma patients, and results of ROC analysis showed that miR-3934 is a sensitive biomarker that can be used to distinguish asthma patients from the healthy volunteers, suggesting it could potentially serve as a diagnostic marker.…”
Section: Discussionmentioning
confidence: 99%
“…Most earlier studies of miR-3934 investigated its role in cancer. For example, it was reported that miR-3934 is up-regulated in colorectal cancer cells [29] and that down-regulation of miR-3934-5p may enhance the sensitivity of A549 non-small cell lung cancer cells to cisplatin by targeting TP53INP1 [30]. Here, we observed that miR-3934 is signi cantly down-regulated in PBMCs from asthma patients, and results of ROC analysis showed that miR-3934 is a sensitive biomarker that can be used to distinguish asthma patients from the healthy volunteers, suggesting it could potentially serve as a diagnostic marker.…”
Section: Discussionmentioning
confidence: 99%